2020
DOI: 10.9734/jpri/2020/v32i1830702
|View full text |Cite
|
Sign up to set email alerts
|

Awareness on Commonly used Sedatives Hypnotic in Dental Practices among Dental Students

Abstract: Fear or anxiety towards dental procedures can discourage patients from getting dental treatment done. The management of anxious patients undergoing dental treatment is still a challenge in clinical practices. The increased use of sedative and hypnotics in dental practices appears to indicate that the assessment of dental student’s awareness of it, is essential. This survey is carried out to determine the awareness of sedatives and hypnotics used in dental practices among dental students. A questionnaire-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
2
1
0
Order By: Relevance
“…In the present study, more than half of the study participants 78.4% preferred Nitrous oxide sedation which is similar to study by Sivakumar N et al (72%) 22 and Wali et al (73%) 1 . These studies have shown that care must be taken when Nitrous oxide sedation is used in addition to other sedatives where the chances of attaining deep sedation in a short span of time are relatively high 1 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the present study, more than half of the study participants 78.4% preferred Nitrous oxide sedation which is similar to study by Sivakumar N et al (72%) 22 and Wali et al (73%) 1 . These studies have shown that care must be taken when Nitrous oxide sedation is used in addition to other sedatives where the chances of attaining deep sedation in a short span of time are relatively high 1 .…”
Section: Discussionsupporting
confidence: 90%
“…In our study, 44.8 % preferred intravenous conscious sedation over oral sedation which is almost similar to the study by Tingey et al (49.8%) 21 but much higher than the study by Sivakumar N et al (3 %) 22 . This variation can be due to case preferences as sedation in children is different from the sedation methods in adults.…”
Section: Discussionsupporting
confidence: 88%
“…Regardless of the procedure's difficulties, postoperative pain is so common that it is frequently used as a tool for researching the quality of analgesia of various medicines or physical techniques. [ 9 10 ]…”
Section: Introductionmentioning
confidence: 99%